An evolving data wise culture (DWC): A case study - Sun, Jingping; Levey, Joyce; Vaux, Nicole (Journal of Interdisciplinary Studies in Education, 2015)
Data-informed instructional decision-making has evolved into an essential process in schools. This feature has not been fully reflected in the school culture constructs developed to date. To reflect this feature, this study examines the extent to which a data-wise culture (DWC) exists in schools and test if the construct that reflects such a culture can be measured. The study finds that there was such a culture existing in the schools in one district. The reliability of the construct DWC was high, indicating that the construct could be a unique variable that deserves further exploration. The DWC survey can be used to evaluate how well school leaders influence school conditions that foster data analysis in schools. This paper calls for the revisit of those cultural variables that have been developed to date in the field of educational leadership to reflect the new feature of data use in schools.